2018
DOI: 10.1123/jab.2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Resistive Forces for Maximizing the Reliability of Leg Muscles’ Capacities Tested on a Cycle Ergometer

Abstract: This study determined the optimal resistive forces for testing muscle capacities through the standard cycle ergometer test (1 resistive force applied) and a recently developed 2-point method (2 resistive forces used for force-velocity modelling). Twenty-six men were tested twice on maximal sprints performed on a leg cycle ergometer against 5 flywheel resistive forces (R1-R5). The reliability of the cadence and maximum power measured against the 5 individual resistive forces, as well as the reliability of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Based on these results, a general recommendation for accurately determining the F–V relationship is to have one point as close as possible to the force-intercept and another point as close as possible to the velocity-intercept. However, it is important to note that the optimal magnitude of the extreme points of the F–V relationship should be carefully determined for each exercise since very extreme points could present a low reliability (e.g., velocities lower than 110 revolutions per minute in the leg cycle ergometer exercise are not recommended; ( García-Ramos et al, 2018a ) and, consequently, their use could compromise the accuracy of the F–V relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, a general recommendation for accurately determining the F–V relationship is to have one point as close as possible to the force-intercept and another point as close as possible to the velocity-intercept. However, it is important to note that the optimal magnitude of the extreme points of the F–V relationship should be carefully determined for each exercise since very extreme points could present a low reliability (e.g., velocities lower than 110 revolutions per minute in the leg cycle ergometer exercise are not recommended; ( García-Ramos et al, 2018a ) and, consequently, their use could compromise the accuracy of the F–V relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been proposed that each subject presents an optimal balance between F 0 and V 0 capacities and, consequently, the ratio between F 0 and V 0 (i.e., F–V slope) can be used to implement individualized resistance training programs ( Morin & Samozino, 2016 ; Samozino et al, 2012 ). Due to the undeniable importance of the outcomes of the F–V relationship (i.e., F 0 , V 0 , F–V slope, and P max ), a number of studies have been conducted to refine the testing procedure of the F–V relationship in different exercises ( Alcazar et al, 2017 ; García-Ramos et al, 2017 , 2018a ; Lemaire et al, 2014 ; Pérez-Castilla et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Future researchers should therefore assess the reliability of the eccentric Fv characteristics measured through a series of DJ tasks. It has recently been shown that the use of the two most distant loads may not be appropriate when using the two-point method to determine the Fv characteristics during a cycling task, as very high loads typically have low reliability [22]. Low reliability in the average force and velocity variables may be expected at greater drop heights, further limiting the drop heights selected when assessing eccentric Fv characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, a general recommendation for accurately determining the F-V relationship is to have one point as close as possible to the forceintercept and another point as close as possible to the velocity-intercept. However, it is important to note that the optimal magnitude of the extreme points of the F-V relationship should be carefully determined for each exercise since very extreme points could present a low reliability (e.g., velocities lower than revolutions per minute in the leg cycle ergometer exercise are not recommended; (García-Ramos et al, 2018a) and, consequently, their use could compromise the accuracy of the F-V relationship.…”
Section: Table 1] [Table 2] [Figure 2] Concurrent Validity Of the F-vmentioning
confidence: 99%
“…In this regard, it has been proposed that each subject presents an optimal balance between F 0 and V 0 capacities and, consequently, the ratio between F 0 and V 0 (i.e., F-V slope) can be used to implement individualized resistance training programs (Morin & Samozino, 2016;Samozino et al, 2012). Due to the undeniable importance of the outcomes of the F-V relationship (i.e., F 0 , V 0 , F-V slope, and P max ), a number of studies have been conducted to refine the testing procedure of the F-V relationship in different exercises (Alcazar et al, 2017;García-Ramos et al, 2017;García-Ramos et al, 2018a;Lemaire et al, 2014;Pérez-Castilla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%